Colossal permittivity in niobium doped BaTiO3 ceramics annealed in N2. (15th March 2018) - Ren, Pengrong; He, Jiaojiao; Wang, Xin; Sun, Mingqiang; Zhang, Hu; Zhao, Gaoyang
Abstract: Nb 5 + and/or In 3 + doped BaTiO3 ceramics were prepared by a conventional solid-state method, followed by annealing in N2 . At the room temperature and 1 kHz, permittivity of Nb 5 + doped BaTiO3 (BTNb) is up to 80, 888 and its dielectric loss is as low as 0.03. The origin of the colossal permittivity in BTNb is ascribed to the giant defect dipoles (Ti 4 +  · e′ − VO  − Ti 4 +  · e′). Besides, (VBa ″  − VO ) defect dipoles are also proved to be present in BTNb, which plays an important role on maintaining lower dielectric loss in a wide temperature region for BTNb. Graphical abstract: Image 2